Application of Neutral Grounding Resistor in High Voltage Photovoltaic Solar Substation System - Chaichan Pothosarn; Theerasak Patcharoen; Panu Srisuksai; Atthapol Ngaopitakkul; A. Kunakorn; Santipont Ananwattanaporn (My University, 2025)
Faults in a distribution system with additional renewable energy sources can lead to unnecessary operation of protection devices due to higher detected fault currents compared to conventional systems. In addition, the voltage at the point of interconnection may temporarily drop to a low level, causing inverter-based generators to disconnect from the system. This study, therefore, proposes an investigation into the use of neutral grounding resistors in a 115 kV high-voltage (HV) substation unit located within a solar power generation system. The approach aims to limit ground fault current and reduce temporary voltage sags to maintain the connection status of inverter and ensure compliance with low voltage fault ride-through (LVRT) capability. The case study is modeled after an actual grid network consisting of two feeders, with one feeder connected to a solar power plant. PowerFactory DIgSILENT software is used to simulate the system and analyze the impact of various neutral grounding resistance values. The results of this study can be applied to the selection of neutral grounding resistors for system, helping to reduce fault current, extend relay operating time within the allowable delay range, and minimize unnecessary tripping of overcurrent protection relays in the system.
Keywords: Power Systems and Renewable Energy